MnO2‐Modified Persistent Luminescence Nanoparticles for Detection and Imaging of Glutathione in Living Cells and In Vivo. Issue 50 (28th October 2014) - Li, Na; Diao, Wei; Han, Yaoyao; Pan, Wei; Zhang, Tingting; Tang, Bo
Abstract Persistent luminescence nanoparticles (PLNPs) hold great promise for the detection and imaging of biomolecules. Herein, we have demonstrated a novel nanoprobe, based on the manganese dioxide (MnO2)‐modified PLNPs, that can detect and image glutathione in living cells and in vivo. The persistent luminescence of the PLNPs can be efficiently quenched by the MnO2 nanosheets. In the presence of glutathione (GSH), MnO2 was reduced to Mn2+ and the luminescence of PLNPs can be restored. The persistent luminescence property can allow detection and imaging without external excitation and avoid the background noise originating from the in situ excitation. This strategy can offer a promising platform for detection and imaging of reactive species in living cells or in vivo.